Problemy tworzenia i funkcjonowania rynku żywności ekologicznej - Łuczka-Bakuła, Władysława; Piasny, Janusz (Wydział Prawa i Administracji UAM, 1997)
Some basic economic problems connected with establishing and development of ecological food market are discussed in the article. The market of ecological food differs fundamentally from the conventional food market when we consider both characteristic features of a product, price level, channels of distribution on one hand, and the buyers bracket on the other. Within this market not only a separate system of labelling the products and special procedures for controlling their production and processing are implemented but also - separate channels of distribution and distinct information system. Though it is a market which is constantly increasing, nevertheless the demand for the products is up to now not big enough to be able to guarantee effective exploitation of specific infrastructure necessary for its further existence and development, i.e. food processing, channels of distribution and information.
Problems of establishing abd functioning of ecological food markets